Modeling Impact of Land Use Dynamics on Hydrology and Sedimentation of Megech Dam Watershed, Ethiopia - Abebe Tarko Assfaw (The Scientific World Journal)
Land use/land cover dynamics change the hydrology and sediment yield of the watershed. This research on how land use dynamics alters catchment hydrology and reservoir sedimentation aids the government to implement appropriate response strategies to minimize undesirable future impacts on the upper Megech dam reservoir. For this study, the impacts were quantified and analyzed through hydrological modeling (SWAT). The overall analysis was performed by using 1998 historical and 2016 recent land use satellite images. The analysis has shown that the cultivated land has increased from 60.69% to 67.17% and urban land from 2.3% to 3.36% between 1998 and 2016. Whereas the grassland area has decreased from 11.42% to 5.33%, plantation forest from 1.84% to 0.9%, and bareland from 3.58% to 2.56%. A comparison of the simulated outputs of the model shows that the mean annual surface runoff for 1998 land use was 251.3 mm and had changed to 316.7 mm in 2016 land use. The mean annual streamflow changed from 150.3 m3/sec to 165.6 m3/sec for 1998 and 2016 land uses, respectively. Similarly, 10.23 t/ha mean annual sediment load gets into Megech dam reservoir in 1998 LULC and was changed to 13.61 t/ha in 2016 LULC. This shows that streamflow, surface runoff, and sediment yield increases by 10.2%, 26.03%, and 33.3% in 2016 land use as compared with 1998 land use. Finally, the most dynamic subbasins that have a significant impact on streamflow and sediment yield were identified. Based on this, subbasins 13, 17, 19, 20, 23, 24, and 25 were found to be the most dynamic and change sensitive subbasins that have a significant contribution to the increment of runoff and sediment yield in Megech dam watershed.